The Influence of Job Placement, Work Experience, and Competence on Employee Performance At PT PLN (Persero) UP3 Pinrang - Anugera Taruna Dewangga; Bahar Sinring; Ramlawati (Economos : Jurnal Ekonomi dan Bisnis, 2024)
Employee performance is one of the essential elements in an organization's success, particularly regarding job placement, work experience, and competence. The objectives of this study are: (1) To determine the effect of job placement on employee performance, (2) To determine the effect of work experience on employee performance. (3) To determine the effect of competence on employee performance. This research employs a quantitative approach using primary data collected through questionnaires distributed to 85 respondents. The study was conducted from January 2024 to February 2024. Data were analyzed using Multiple Regression Analysis with the assistance of SPSS Version 25. The results of this study indicate that: (1) Job placement has a significant effect on employee performance. (2) Work experience has a significant effect on employee performance. (3) Competence has a significant effect on employee performance. Simultaneously, job placement, work experience, and competence significantly influence employee performance.